The Peppermill: a Human-powered User Interface Device - Villar, Nicolas; Hodges, Steve (Proceedings of the Fourth International Conference on Tangible, Embedded and Embodied Interaction, 2010)
A human-powered user interface device sources its power from the physical effort required to operate it. This paper describes a technique by which a geared DC motor and a simple circuit can be used to enable interaction-powered rotary input devices. When turned, the circuit provides a temporary power source for an embedded device, and doubles as a sensor that provides information about the direction and rate of input. As a proof of concept, we have developed a general-purpose wireless input device – called the Peppermill – and illustrate its capabilities by using it as a remote control for a multimedia-browsing application.